PORTRAIT OF SEXUAL HARASSMENT VICTIMS AND RELIGIOUS SUPPORT OF THE PARENTS IN ACEH - Salami, Salami; Fadhilah, Fadhilah; Jannah, Miftahul; Inayatillah, Inayatillah (SCAD Independent, 2020)
Parental religious education is the most important thing in educating and raising children. The religious education that parents have will influence the norms and behavior of children to be educated and mature individuals. But now, even though parents understand the religious values, it is still difficult to implement these values in the family, especially in controlling the interaction of their children. This study investigated the religious value of parents in raising their children and the solution they offer to solve the problem related to sexual harassment issues faced by the children. This study used interviews, documentation, and observation, conducted in three locations namely in Bireuen district with four families, in North Aceh with three families, in Pidie Jaya with seven families, a total of all 14 families. The survey results in Bireuen showed even though their children suffered sexual harassment and rape but the parents were still able to hold their emotions because they had a strong religious education. They were happy to have children because it was assumed that they came from intact families. There is a stigma of society that their children are victims of sexual violation, whereas their parents have a good religious education. Complete intact families that still have both parents, can bring happiness, comfort, protect, and communicate well with their children. Otherwise, incomplete families whose children suffered sexual abuse victims are difficult to solve the problems being faced, especially to cheer up their children.